Insects role changes in streams under shifting environment and climate - Gutiérrez, Carolina, author; Harrington, Rachel, author; Kondratieff, Boris, author; Webb, Colleen, author; Ghalambor, Cameron, author; Poff, N. LeRoy, author (Colorado State University. Libraries, 2017)
Functional diversity quantifies the value and range of organismal traits influencing species roles and performance in ecosystems. Aquatic insect functional diversity has been examined previously, but not in the context of strong environmental and climate gradients. We quantified and tested differences in three primary components of functional diversity of stream insects along an altitude gradient: Functional Richness (FRic), Functional Evenness (FEve) and Functional Divergence (FDiv). 24 small streams in three adjacent basins were studied; spanning an elevational range of 2000-3500 m. Our results showed that only FRic differs significantly with altitude, and this pattern of change remains constant across basins.
121 - Carolina Gutierrez
Poster presented at the 2017 Graduate Student Showcase at CSU, and awarded one Top Scholar for University-Wide Graduate Programs award, presented and offered by the Graduate School.
Keywords: aquatic insects; functional diversity; stream ecology; elevation gradient; latitude gradient